2016
DOI: 10.5713/ajas.16.0372
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium-rich yeast supplementation on the plasma progesterone levels of postpartum dairy cows

Abstract: ObjectiveThe effects of the pre- and postpartum supplementation of cows with Se on their plasma P4 concentrations after calving were investigated.MethodsThirty-four Holstein cows were used to investigate the effects of dietary selenium supplementation on the postpartum recovery of the luteal function in cows. Selenium-rich yeast (containing 300 ppm selenium) was mixed with total mixed ration fed to 17 pregnant cows from 30 days before they were due to calve (10 g yeast daily) to 100 days after calving (20 g ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 36 publications
(47 reference statements)
2
18
1
6
Order By: Relevance
“…The results of the current study disagreed with Zeitoun et al, (19) that giving low and high doses of arginine to pregnant ewes at the early pregnancy led to a decrease in the level of estrogen at the early pregnancy, Soleimanzadeh et al, (16) observed a rise in estrogen level when injecting selenium with vitamin E late pregnancy.…”
Section: -Concentration Of the Estrogen (Table-3)contrasting
confidence: 99%
See 1 more Smart Citation
“…The results of the current study disagreed with Zeitoun et al, (19) that giving low and high doses of arginine to pregnant ewes at the early pregnancy led to a decrease in the level of estrogen at the early pregnancy, Soleimanzadeh et al, (16) observed a rise in estrogen level when injecting selenium with vitamin E late pregnancy.…”
Section: -Concentration Of the Estrogen (Table-3)contrasting
confidence: 99%
“…This indicates that dietary supplements of arginine and selenium with vitamin E act to protect the corpus letum and progesterone from oxidation and regulation programmed death of the corpus letum and prevent hyperplasia of the corpus letum result in an increase in the concentration of progesterone, especially as increase was accompanied whith the progress of pregnancy days in ewes. The results of the study agreed with Yildiz et al, (15) whom observed that injecting vitamin E at the early pregnancy leads to increased concentration of progesterone (16). Kamada (17) observed when giving selenium the progesterone increased its concentration (P≤0.05) at late pregnancy.…”
Section: Effect Of Arginine 160 μMol Selenium and Vitamin E 2 ML On supporting
confidence: 90%
“…Khatti et al, (2017) reported that supplementation of Se (0.3 mg/kg DM) and Vitamin E (80 IU/kg DM) along with 20% additional allowance for energy to the advance pregnant cross bred cow results in significantly higher pregnancy rate and early resumption of postpartum estrus in treated animals as compared to control. Kamada (2017) reported that postpartum plasma progesterone concentrations was higher in selenium yeast (300 mg Se, 10 g yeast) supplemented Holstein cow the control.…”
Section: Selenium (Se)mentioning
confidence: 97%
“…The results were consisted with Soliman (18).There was no significant difference between selenium vitamin E and albumin concentration and was 3.2 in both groups. Kamada (15) observed that albumin in blood plasma was not significantly affected when selenium was given at the late pregnancy. Li et al, (20) clamed there were no significant differences between the Arginine group and control in albumin concentration.…”
Section: -Albumin Concentration (Table -3)mentioning
confidence: 99%